2020
DOI: 10.1080/09637486.2020.1852192
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry benefits to cognitive function across the lifespan

Abstract: It is well known that what we eat can influence our physical wellbeing, but interest is also increasing in the relationship between our diet and cognitive health. In recent years, blueberries have risen from relative obscurity to superfood status following a number of published epidemiological studies, rodent trials, and human RCTs, that suggest blueberries may convey benefits to cognition and mood. This commentary explores some of the evidence in humans, particularly during periods of cognitive development in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Several systematic reviews have provided qualitative assessment of the current research showing promise for the positive cognitive effects of flavonoids. [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] However, the few quantitative meta‐analyses that have been conducted have been limited to specific populations or particular flavonoid‐rich food sources, resulting in conclusions regarding cognitive effects that cannot be generalized more widely to broader populations or applied to other flavonoid‐containing foods. [ 26 , 27 , 28 , 29 , 30 , 31 ] Further, in light of recent reports showing only 33% of the adult population in the UK consumes five or more portions of fruits and vegetables a day, [ 32 ] such targeted meta‐analyses do not address the wider health benefits of consuming a range of beneficial plant‐based foods in line with government dietary recommendations such as the UK's “5‐ a day” and “eat the rainbow” campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews have provided qualitative assessment of the current research showing promise for the positive cognitive effects of flavonoids. [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] However, the few quantitative meta‐analyses that have been conducted have been limited to specific populations or particular flavonoid‐rich food sources, resulting in conclusions regarding cognitive effects that cannot be generalized more widely to broader populations or applied to other flavonoid‐containing foods. [ 26 , 27 , 28 , 29 , 30 , 31 ] Further, in light of recent reports showing only 33% of the adult population in the UK consumes five or more portions of fruits and vegetables a day, [ 32 ] such targeted meta‐analyses do not address the wider health benefits of consuming a range of beneficial plant‐based foods in line with government dietary recommendations such as the UK's “5‐ a day” and “eat the rainbow” campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, blueberries have risen from relative obscurity to super food status following a quantity of published epidemiological researches, rodent trials, and human, that recommends blueberries may convey benefits to cognition and mood. Actions are seen following dose sizes easily achievable within a usual diet [32,[179][180][181]. The high antioxidant potential of blueberry extracts has been linked with the improvement of aging symptoms [179].…”
Section: Examples Of Polyphenolic-food: Anti-aging Super Foodmentioning
confidence: 99%
“…Actions are seen following dose sizes easily achievable within a usual diet [32,[179][180][181]. The high antioxidant potential of blueberry extracts has been linked with the improvement of aging symptoms [179]. Galli et al have observed, in the hippocampus of rats, that supplementation with a cranberry extract may reverse the age-related decline of the heat shock protein [182].…”
Section: Examples Of Polyphenolic-food: Anti-aging Super Foodmentioning
confidence: 99%
“…Epidemiological studies have reported that higher dietary intake of flavonoids is associated with slower rates of cognitive decline ( 6 8 ) and dementia ( 9 ). Foods rich in anthocyanins (responsible for imparting the red, purple and blue colour to several fruits and vegetables) and proanthocyanidins such as berries are consistently shown to improve cognition ( 10 13 ), and are further supported by a wealth of preclinical data ( 14 19 ), as well as emerging clinical evidence with fruit juices ( 20 , 21 ) and freeze-dried fruit powder ( 22 24 ). Potential mechanisms include an enhancement of neuronal signalling and synaptic plasticity ( 17 , 25 ), a modulation of glucose metabolism/insulin resistance ( 26 , 27 ), a change in microbiota diversity and metabolism ( 28 30 ) along with regional increases in cerebral perfusion ( 31 34 ), however, further elucidation is required.…”
Section: Introductionmentioning
confidence: 97%